2016
DOI: 10.1016/j.jmb.2015.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into KCTD Protein Assembly and Cullin3 Recognition

Abstract: Cullin3 (Cul3)-based ubiquitin E3 ligase complexes catalyze the transfer of ubiquitin from an E2 enzyme to target substrate proteins. In these assemblies, the C-terminal region of Cul3 binds Rbx1/E2-ubiquitin, while the N-terminal region interacts with various BTB (bric-à-brac, tramtrack, broad complex) domain proteins that serve as substrate adaptors. Previous crystal structures of the homodimeric BTB proteins KLHL3, KLHL11 and SPOP in complex with the N-terminal domain of Cul3 revealed the features required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
97
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(116 citation statements)
references
References 55 publications
12
97
0
Order By: Relevance
“…Thereby, our data add for the first time ZBTB38 to the short list of BTB-domain proteins that were recently shown to not bind to cullin-3 [59, 60]. …”
Section: Discussionmentioning
confidence: 87%
“…Thereby, our data add for the first time ZBTB38 to the short list of BTB-domain proteins that were recently shown to not bind to cullin-3 [59, 60]. …”
Section: Discussionmentioning
confidence: 87%
“…Solved structures are available for the N‐terminal BTB domain of several KCTD family proteins primarily revealing pentameric homo‐oligomers. This fivefold symmetry appears to extend through the C‐terminus . The BTB domains of KCTD proteins also mediate other protein‐protein interactions, leading to three main hypotheses for general KCTD mechanisms.…”
Section: Structure and Function Of Kctd Family Proteinsmentioning
confidence: 99%
“…The distinguishing feature of KCTD proteins is a single N‐terminal BTB/POZ (bric‐a‐brac, tramtrak, and broad complex/poxvirus zinc finger) domain, the exception being KCTD19 with three separate BTBs that may reflect tandem gene amplification (Figure ) . BLAST searches readily reveal that the BTB domains of KCTD family proteins are most similar in amino acid sequence to the T1/BTB domains that mediate tetramerization of voltage‐gated potassium channel subunits to form functional channels . This sequence similarity to Kv channels explains how KCTDs acquired their official name (potassium channel tetramerization domain).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its name, KCTD17 has been shown to act as a substrate-adaptor for Cul3-RING ubiquitin ligases (CRL3s) to regulate proteosomal degradation of specific targets. 22, 36, 37 We observed that hepatic Kctd17 expression is robustly increased in HFD-fed and db/db mice (Figure 4A). Next, we confirmed our LC-MS/MS results by immunoprecipitation of endogenous KCTD17 in livers from HFD-fed mice with anti-PHLPP2 antibody, and vice versa (Figure 4B).…”
Section: Resultsmentioning
confidence: 88%